The Investigation of Curing Process on Synthetic Leather Substrates - Ismail, Nur Atirah Atasha; Khirotdin, Rd. Khairilhijra (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Synthetic leather is a durable material with a similar appearance and durability to real leather at a lower cost, most commonly used in the printing industry for many purposes. Over the past several decades, ultraviolet printing (UV) has shown great potential in synthetic leather printing with good speed and quality. However, some drawbacks were found, including graphical structure can crack or quickly pull down on the synthetic leather surface. UV ink is not fully cured, causing materials to remain sticky or wet to the touch after the printing. Not to mention, UV ink giving an unpleasant odour and cause some health problems due to over-exposure to UV light. Therefore, based on the full factorial design of the experiment's method (DoE), a predictive model using Minitab software was used to characterizing and optimizing the curing parameters for the curing process on PVC synthetic leather substrates. Then, validate the results using existing curing techniques, Delone M2 – 1800. This contribution evaluates the optimum level for input parameters correspond to line width and pattern edge response values. The obtained results from Minitab software show curing temperature at 50°C, 60°C, and 70°C, and curing time at VSD_2, VSD_3, and VSD_4 are significant for curing the PVC synthetic leather substrates.